PENGARUH TEKANAN KETAATAN, INDEPENDENSI, PENGALAMAN KERJA, LOCUS OF CONTROL TERHADAP AUDIT JUDGMENT DI KAP BALI - Pertiwi, Kadek Upawita Candra; Budiartha, Ketut (E-Jurnal Akuntansi, 2017)
R esearch was conducted in public accounting firm in the area of ??Bali with the primary data collection method using  questionnaire. S amples analyzed by 33 respondents, and research using purposive sampling method. D ata have been valid and reliable, meet the classic assumption test, and analysis techniques used were multiple linear regression analysis using SPSS . The final result of the study states that stress obedience and locus of control have negative effects on audit judgment. Auditor independence and work experience positive effect on audit judgment. It can concluded that to obtain audit judgment are accurate, an auditor must be able to face the pressure obtained from seniors and their clients and keep the nature of external locus of control which is owned by the individual auditor, and to obtain audit judgment accurate an auditor have an independent nature high with no partiality to any entity and enhance the work experience they have.
Keywords: Pressure Obedience, Independence, Job Experience, Locus Of Control, Audit Judgment